2002
DOI: 10.1136/gut.50.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori stimulates pepsinogen secretion from isolated human peptic cells

Abstract: Background: Different acid and peptic related gastroduodenal diseases are associated with both increased gastric secretion and Helicobacter pylori infection. Patients with H pylori associated gastritis or duodenal ulcer have increased serum pepsinogen levels which decrease after eradication. The mechanisms of H pylori induced gastric mucosal damage are not completely understood. Aim: To determine the effects of H pylori on pepsinogen secretion from isolated human peptic cells. Methods: Dispersed human peptic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 26 publications
6
40
1
Order By: Relevance
“…32,33 We assume that the correlation between PG levels and histological atrophy is weakened by the combined effect of these three factors prior to eradication, whereas inflammation and H. pylori would have no ongoing effect after eradication, and thus the correlation between PG and atrophy would thereby be strengthened. In other words, prior to eradication, PG is released from chief cells in response to inflammation and H. pylori, or enters the blood in large amounts because of the destruction of chief cells.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 We assume that the correlation between PG levels and histological atrophy is weakened by the combined effect of these three factors prior to eradication, whereas inflammation and H. pylori would have no ongoing effect after eradication, and thus the correlation between PG and atrophy would thereby be strengthened. In other words, prior to eradication, PG is released from chief cells in response to inflammation and H. pylori, or enters the blood in large amounts because of the destruction of chief cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gastric mucosal inflammation increases secretion of PGI and PGII from the chief cells, caused by cytokines, signal mediators, or H. pylori infection. [21][22][23] These could explain various cut-off values of serum PG profiles in different populations. For instance, in Japan, the proposed cut-off points to determine atrophy and gastric cancer risk are 70μg/L for PGI and 3.0 for PGI/II ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of H. pylori, either addressed by serological evaluation or by immunohistochemistry in bioptic specimens, seems to increase pepsinogen I and II levels and decrease pepsinogen I/II ratio in conjunction with inflammation. [72][73][74] As suggested, no modifications in cut-off of pepsinogen test, or the inclusion of H. pylori serology, were reported or showed any improvements. Some authors 43,74 showed that the decrease of pepsinogen I/II ratio is independent of the presence of H. pylori.…”
Section: Discussionmentioning
confidence: 99%